2013
DOI: 10.1136/bcr-2013-009434
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal bone cyst of temporal bone

Abstract: SUMMARYAneurysmal bone cysts (ABC) are benign neoplasms frequently occurring in the long tubular bones. It is very rare in temporal bone. We report a case of ABC of the left temporal bone in an 8-year-old Asian boy who presented clinically with swelling over the left temporal region for 5 months. CT and MRI features were suggestive of ABC. Surgical resection was performed and on follow-up the patient was doing well. CT and MRI are the imaging modalities for proper evaluation of ABC, aiding to diagnosis and hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Radiologically, they have a characteristic expansile bony growth on head CT with multiple septations. MRI shows an extraaxial lesion with a soap-bubble appearance on T2W images, having fluid levels representative of blood inside the bony septa and ballooning of the bone [3]. Rarely they may have infiltration of the dura as well.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Radiologically, they have a characteristic expansile bony growth on head CT with multiple septations. MRI shows an extraaxial lesion with a soap-bubble appearance on T2W images, having fluid levels representative of blood inside the bony septa and ballooning of the bone [3]. Rarely they may have infiltration of the dura as well.…”
Section: Discussionmentioning
confidence: 97%
“…Two forms of ABCs have been described, primary and secondary, with secondary lesions seen in association with non-ossifying fibroma, giant cell tumor, chondroblastoma, fibrous dysplasia, and so on [3]. Lichtenstein suggested that ABCs could result from a local circulatory disturbance because of sudden vascular occlusion of venous drainage of that segment of the bone or development of an arterio-venous shunt.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…19 In our review of temporal bone ABCs, we noted that the petrous portion of the temporal bone was the most commonly involved site and that ABCs rarely extended to more than 1 portion of the temporal bone. Three cases described ABC involvement of the petrous and squamous portions, 7,15,16 with no prior reports of concurrent involvement of the mastoid, petrous, and squamous portions.…”
Section: Discussionmentioning
confidence: 99%
“…This report is the ninth histologically confirmed case of ABC of the temporal squamosa in the English literature 7,[10][11][12][13][14][15][16] and the first report of ABC of any subtype involving the petrous, mastoid, and squamous portions of the temporal bone. This is also the first reported case of SVABC of the temporal bone.…”
Section: Introductionmentioning
confidence: 99%